Personal and Social Skills’ Impact on Marketing Effectiveness - Mousli Liza; Larras Chafika; Bouchetara Mehdi; Iraten Sabrina (Marketing of Scientific and Research Organizations, 2023)
This study examines the importance of emotional intelligence (EI) in marketing among professionals in the Algerian telecommunications industry. EI plays a crucial role in building strong relationships, effective communication, and connectionbuilding, especially as technology and AI advance. However, there is limited research on EI in marketing professionals within telecommunications. Using a quantitative survey and regression analysis, the study finds a positive impact of EI dimensions on marketing effectiveness. These findings have implications for improving marketing team performance by implementing training programs that enhance EI skills. The study contributes to the scientific community by emphasising the significance of EI in marketing and encouraging further research.